About identity of law in relation to its quality - Kaźmierczyk, Stanisław (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
The contents of this study is a reflection of an idea of the law identity from a perspective of issues in the ontology of law and its legitimization. The author underlines difficulties that are of epistemological and methodological nature in relation to a possibility of recognition and exhaustive determination of the idea. The author also indicates to a crisis of social assessment of law and by the same token its value . A change in this assessment is viewed as an increase in its broadly understood quality.